Personal Role in the Mediation of Entrepreneurship Education on Interest in Entrepreneurship - Rismawati Rismawati; Nurhaedah Nurhaedah; Syed Norris (Universitas Muhammadiyah Ponorogo, 2023)
This study has a purpose to analyze (1) To find out and explain the influence of Entrepreneurship Education on Personal Management Students S1 at Stiesia Surabaya, (2) To find out and explain the Personal Influence on Interest in Entrepreneurship, (3) To find out and explain the influence of Entrepreneurship Education on Entrepreneurial Interests of Management S1 Students at Stiesia Surabaya, (4) To find out and explain the influence of Personal roles in mediating Entrepreneurship Education on Entrepreneurial Interests of Undergraduate Management Students at Stiesia Surabaya. This research belongs to the type of research in the category of explanatory research, which is to explain a relationship between variables through hypothesis testing. The research sample amounted to 125 people. The sample in this study using the census method. In order to analyze the data the author uses the statistical technique Partial Least Square (PLS). The results of the research from the results of data analysis using the statistical partial least square (PLS) technique which can be seen from the results of data analysis which states that Entrepreneurship Education has a positive and significant influence on Personal, Personal can have a positive and significant influence on Entrepreneurial Interest. positive and significant influence on Entrepreneurial Interest and Entrepreneurship Education indirectly (through the Personality variable) significantly influence the Entrepreneurial Interest of S1 Management Students at Stiesia Surabaya.